The fruit and vegetable sector in Ecuador: Main socio-productive characteristics of the agri-food network of Cape gooseberry (Physalis peruviana) (2019)
Although in Ecuador the fruit and vegetable sector has shown growth in local and international markets, it has also faced socio-economic and productive challenges in its structure and articulation that have not been analyzed so far; such is the case of the agri-food network of Cape gooseberry, located in the central Andean area of ​​the country. In this sense, the present study shows the main socio-productive characteristics of the agrifood network mentioned, the identification of stages, agents and activities (primary and support), and the analysis of the mechanisms that govern it; for which a systemic methodology was used to characterize the aforementioned network, and where it was determined that it has advantages such as the inclusion of women in the productive stage, and the sense of associativity of processors and distributors. On the other hand, it was concluded that producers require training in topics such as post-harvest, transportation logistics, and food quality. Likewise, it is necessary to strengthen associative structures that encourage greater participation of agents in the production stage. Finally, it was deduced that the network requires to increase the cultivation area, and the application of greenhouse production systems to increase yields, with the purpose to achieve advantages in international markets.